2022
DOI: 10.24193/jebp.2022.1.5
|View full text |Cite
|
Sign up to set email alerts
|

"Post-traumatic Stress Disorder and Difficulties in Emotion Regulation Among University Students under the COVID-19 Condition"

Abstract: "The new global situation of COVID-19 affects the whole world in all aspects of life including mental health. The study’s goal is to detect the relationship between post-traumatic stress disorder (PTSD) and Emotion Regulation (ER) difficulties under the COVID-19 condition. Methods: University students were asked to complete: 1) Emotion Regulation Difficulties Questionnaire (DERS) 2) PTSD Checklist (PCL- 5). 3) Life Events Checklist for DSM-5 (LEC-5). Results: There were 441 students with suspected COVID-19 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
0
3
0
1
Order By: Relevance
“…Pesquisas chinesas, realizadas no ano de 2020 com estudantes de instituições superiores da China, encontraram, à análise da consistência interna da PCL-5, um Alfa de Cronbach de 0,96 (Yang et al, 2022;Zhen et al, 2022), mesmo número verificado para nossa escala global, corroborando os achados aqui apresentados. Elbarazi (2022), em estudo aplicado com universitários residentes no Egito, obteve um Alfa de 0,93 para a referida escala, quantia esta que se enquadra abaixo das percebidas neste trabalho, mas mantém-se na faixa de valores atribuídos a uma consistência interna de caráter adequado.…”
Section: Item N M Dp Cv Mín-máxunclassified
“…Pesquisas chinesas, realizadas no ano de 2020 com estudantes de instituições superiores da China, encontraram, à análise da consistência interna da PCL-5, um Alfa de Cronbach de 0,96 (Yang et al, 2022;Zhen et al, 2022), mesmo número verificado para nossa escala global, corroborando os achados aqui apresentados. Elbarazi (2022), em estudo aplicado com universitários residentes no Egito, obteve um Alfa de 0,93 para a referida escala, quantia esta que se enquadra abaixo das percebidas neste trabalho, mas mantém-se na faixa de valores atribuídos a uma consistência interna de caráter adequado.…”
Section: Item N M Dp Cv Mín-máxunclassified
“…Everyone may have experienced at least one traumatic incident or terrible adversity in their lives, however, not everyone suffers from PTSD as a result (Young, 2017). Since women are more likely to be raped and sexually abused, they experience depression, anxiety, eating disorders, and insomnia (Hyland et al, 2020; Price et al, 2019; Scharff et al, 2019).…”
Section: Symptoms Of Ptsdmentioning
confidence: 99%
“…According to McNamara (2010), a study was conducted on 70 women who had PTSD, and it was discovered that each of these women had an average of 2.5 children, indicating that having this disorder may harm their children, since they may also have depression. As per Young (2017), extensive research has demonstrated that women who have had a traumatic incident during their pregnancy will alter the development of their child, and in many circumstances, this will have lasting consequences throughout the child’s life.…”
Section: Effects Of Ptsd On Womenmentioning
confidence: 99%
“…The campus lockdown measures adopted by colleges and universities have brought many challenges to college students ( 49 ), such as irregular living habits, low learning efficiency, and difficulties in affect regulation ( 50 ), which has directly posed a great threat to the physical and mental health of college students. The benefits of physical exercise (PE) in improving the neuroendocrine system and the immune system, promoting mental health, and anti-anxiety have been proven ( 51 ).…”
Section: Introductionmentioning
confidence: 99%